Penerapan Kecerdasan Buatan Dalam Peningkatan Efektivitas Rekrutmen: Studi Kasus Pada Perusahaan Outsourcing - Tuffah Kurrotu Akyuni Putri; Alif Sulthon Basyari (Pascasarjana STIE Amkop Makassar, 2026)
The Industry 5.0 era demands organizations to integrate technology and human roles for business sustainability. This study aims to analyze the implementation of Artificial Intelligence (AI) through the n8n workflow automation platform in enhancing recruitment effectiveness at an outsourcing company in Gresik. The research method used is descriptive qualitative, with data collection techniques including unstructured interviews, participatory observation, and documentation during internship activities. The results indicate that the integration of n8n and Gemini AI is capable of automating mass CV screening, increasing selection process speed, and reducing the administrative burden of the HR division. Nevertheless, technical constraints were found in the form of non-uniform document formats and the need for manual verification to ensure final accuracy. This study concludes that AI serves as a significant decision-support tool but still requires human supervision to maintain selection quality. Keywords: Artificial Intelligence, Recruitment, n8n, HR Effectiveness, Outsourcing.